PARTISIPASI MASYARAKAT DALAM PERENCANAAN DAN PELAKSANAAN PEMBANGUNAN DESA DI DESA HILIFAONDRATO KECAMATAN LOLOMATUA KABUPATEN NIAS SELATAN - Philipus Noverman Giawa; Marlan Huthaean; Artha L Tobing (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
Community participation is a crucial factor in the success of village development. Community involvement is necessary not only in the development implementation phase but also in the planning and decision-making process. This study aims to analyze community participation in development planning and implementation and to identify factors influencing community participation in Hilifaondrato Village, Lolomatua District, South Nias Regency. This study used a qualitative approach, with data collection techniques through interviews, observation, and documentation. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing (Miles & Huberman, 2014). The results indicate that community participation in the planning phase was carried out through village deliberation forums, but this participation remained consultative in nature. Meanwhile, community participation in the development implementation phase demonstrated a higher level of involvement through mutual cooperation activities, material contributions, and social support for village development activities. Factors influencing community participation include social awareness, community economic conditions, village government communication, and transparency in development implementation.